ANALYSIS OF CAVED MODELLING WITH STRONG ROCK AND WEAK ROCK IN BLOCK CAVING MINING METHOD - BARRA VICRA, AHMAD
Continuous caving is one of important factor for the success of a block caving operation. The caving process can be modelled by using Finite Elements Method (FEM) Modeling with method elements is completed by considering mass rock strength. The parameter that are analyzed is Factor of Safety by identifying the value of sigma 1 dan sigma 3. From the results of modeling, 5th ButcherÃ‚Â’s rule (1999) that stated that the advance of the caving made from weak to strong to achieve continuous rock caving as quickly as possible is proven. This is done so that the stress on the face of the hydraulic radius increases with the undercut as needed and also reduce the level of induced stress on the end ruins. From the results of modelling, it is also proved that the bigger the hydraulic radius, the bigger chance of a mass rock to cave.